(3GdCMcGe aj GdMSHI GdTQjaIs - (3Ydj Hf eMeO MHjH, CHh GdMSf GdeGhQOj,J (B450 (3g` s ((3eMeO GdTGPdi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM UOhQ GdYGQajf GdeMJSHjf Hg hCTgO Cf dG Edg EdG Gddg jTJed Ydi bhGYO Gdbhd hCHhGH haUhd fHgJ ajg Ydi eUfhYGJ Cgd GdMQa aGSJNQJ Gddg ai Pdc hVefJg HGdfbd hGdGLGO s
(3BNQgG (B:s
(3aEfg ef hXGFag hEdRGeg aeJi aQW ajg hRQg Ydjg hHGddg GdeSJYGf hYdjg GdJcdGf hdG Mhd hdGbhg EdG HGddg GdYdi GdYXje ced cJGH GdGMcGe HMeO Gddg hYhfg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdSjGSI hGdGLJeGYs